Inoculation of Scytalidium thermophilum in Button Mushroom Compost and Its Effect on Yield - Straatsma, Gerben (1994)
Scytalidium thermophilum isolates in culture, as well as the endogenous strain(s) in mushroom compost, were inactivated at 70°C. This temperature was used to pasteurize composts for experiments. Of nine thermophilic fungal species, only S. thermophilum and Myriococcum thermophilum grew well on pasteurized compost in test tubes. The effect of both species on the crop yield of Agaricus bisporus mushrooms was studied. In solid-state fermentation rooms called tunnels, compost was pasteurized and inoculated. After incubation, the inoculated organisms were reisolated and counted, showing their successful colonization. The yield of mushrooms on inoculated composts was almost twice that on the pasteurized control. This result demonstrates the effectiveness of S. thermophilum in compost preparation. Inoculation is not necessary for traditional compost preparation. Naturally occurring strains of S. thermophilum, present in ingredients, readily colonize compost during preparation. Inoculation may be vital if compost is pretreated at a high temperature in tunnels. This finding is of relevance for the environmentally controlled production of high-yielding compost.